Astronomy, Literary Criticism, and Medieval Literature: An Introduction (Interfaces: A Journal of Medieval European Literatures, 2021)
Dale Kedwards introduces Cluster 1 of Interfaces 8, on the topic of The Astronomical Imagination in Literature through the Ages.
Keywords: Chaucer; Christine de Pizan; dream of Scipio; medieval astronomy; Macrobius